ANALISIS KELAYAKAN BISNIS PADA RESTORAN HAN’S FRIED CHICKEN DI KABUPATEN BOJONEGORO DITINJAU DARI ASPEK PASAR DAN PEMASARAN - Rida Irmanda; Abdur Rohman (Department of Sharia Economics, Faculty of Islamic Economics and Business, Universitas Islam Ibrahimy Banyuwangi, Indonesia, 2024)
The problem discussed in the journal is how business feasibility is viewed in terms of market and marketing aspects at the Han's Fried Chicken Restaurant in Bojonegoro Regency. And the focused benefit of this research is to find out whether the Han's Fried Chicken Restaurant on Jl. East Youth No.116 Kadipaten, Kec. Bojonegoro, Bojonegoro Regency, East Java, whether it is worth running or not. Because every aspect that is an indication in a business feasibility study must meet certain standards. The analytical method used is a descriptive qualitative approach, where this scientific method is used to build knowledge through understanding and discovery based on aspects of business feasibility studies, namely market and marketing aspects. The results of this research show that the Han's Fried Chicken Restaurant is worth carrying out reviews from marketing and market aspects by relying on promotions and the food menus served are quite varied and the prices are very pocket friendly.